A Tailored Intervention for PAP Adherence: The SCIP-PA Trial. Issue 1 (2nd January 2019) - Sawyer, Amy M.; King, Tonya S.; Weaver, Terri E.; Sawyer, Douglas A.; Varrasse, Miranda; Franks, Jamie; Watach, Alexa; Kolanowski, Ann M.; Richards, Kathy C.
ABSTRACT: Objective/Background : Positive airway pressure (PAP) is highly efficacious treatment but nonadherence is prevalent with little improvement over the last 15 years. Tailored interventions show promise for promoting adherence to other treatments. The study objective was to examine feasibility and acceptability of a tailored intervention to promote PAP adherence. Participants : The convenience sample met inclusion criteria: newly diagnosed OSA; treatment-naïve; ≥ 18 years. Exclusion criteria: previous obstructive sleep apnea (OSA) diagnosis and treatment; new psychiatric diagnosis; use of oxygen/bilevel PAP; secondary sleep disorder. Adults ( n = 118) were randomized to tailored intervention (TI; n = 61) or usual care (UC; n = 57); application of a priori exclusion criteria resulted in 30 participants per assignment who were middle-aged (51.3 ± 11.1 years) adults (70% male) with severe OSA (apnea hypopnea index [AHI], 35.9 ± 25.2). Methods : Randomized, double-blind, single-site pilot controlled trial. A multiphased tailored intervention targeting social cognitive perceptions of OSA–PAP treatment was delivered at four intervals. Descriptive analysis, group differences, and self-efficacy change scores by t -test, and thematic analysis of acceptability data are reported. Results : One-week PAP use among TI was 35 min greater than UC condition ( p = 0.20; Cohen's d = 0.336). Treatment use decreased at 1 month and 3 months (NS). Per-protocol delivery of face-to-face intervention delivery was 100% but lower for telephone intervention delivery. Personalized approach was valued by participants. Conclusions : A tailored intervention approach is acceptable to participants and feasibly implemented in a clinical sleep center setting. The intervention effect size at 1 week is consistent with other educational PAP adherence interventions but was not sustained; further pilot testing is warranted to address pilot RCT limitations.